Awareness, attitude and practice of contraception amongst post-partum women in a rural tertiary care hospital, Telangana, India - Murty, Nabhi V. R.; M., Madhuri; G., Vijayalakshmi; K., Vasantha; K., Kavitha; B., Uma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India was the first country in the world to start the National Family Welfare Program in 1951. But population stabilization has been a difficult target to achieve and by the year 2028, our population is expected to surpass that of China. This study was conducted among puerperal women delivered at our hospital to know their awareness about various methods of contraception and willingness to practice any of these methods. Methods: This cross-sectional interview-based study was conducted in the department of obstetrics and gynecology at Bhaskar Medical College and Hospital, Moinabad, Hyderabad from September 2015 to August 2016. The study sample were women who delivered in our hospital and a set questionnaire was used. Results: A total of 502 women in the post-partum period were included in the study.88.85% women were aware of any modern contraceptive. 30.85% of these women were aware of only the surgical method, i.e. sterilization; and another 58% women were aware of temporary methods also. Most of them knew about multiple methods, but tubectomy was the main method was known to the maximum (78%). As the literacy levels rose, awareness about temporary methods and male sterilization also increased. 70% of the study population were not aware of free availability of all these methods at Government hospitals and at our hospital.80.5% of these women were motivated after this study to accept a contraceptive method. Conclusions: There is a great unmet demand for contraception among rural women in India. Proper dissemination of the information about free availability of these methods by rural health workers, hospital staff and making these accessible in the peripheral areas of the country will help these couples. Providing oral, written and visual information to all the pregnant women at each ante-natal visit will be additional methods.